If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3 + 5x) + -1 = 89 (3 * 5 + 5x * 5) + -1 = 89 (15 + 25x) + -1 = 89 Reorder the terms: 15 + -1 + 25x = 89 Combine like terms: 15 + -1 = 14 14 + 25x = 89 Solving 14 + 25x = 89 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 25x = 89 + -14 Combine like terms: 14 + -14 = 0 0 + 25x = 89 + -14 25x = 89 + -14 Combine like terms: 89 + -14 = 75 25x = 75 Divide each side by '25'. x = 3 Simplifying x = 3
| 10-2a+4=32 | | 3=-4n+3n | | 2(j-3)=9(6-3j)+10j | | 9x^2+26x+17=0 | | 3p+6=2p+10 | | 20(y+2)=4y+5 | | 2j-6=54-27j+10j | | x-34=-14 | | 4X-30+X+20=180 | | 8x^3-60x^2+150x-854=0 | | x-27=-17 | | -27=-5(9a+6) | | 12+8r=6-10r | | 10x+3(4x-2)=6 | | 7y+3(y-6)=6(y+1)-3 | | 12x-(8x-9)=45 | | 6x-7x+2=12 | | 2x-8+10=3x-7 | | 5*sin(14x)=5*cos(7x) | | 13x^2-8x-20=0 | | -2y+9x=3 | | -14+74=-5(x+3) | | 3y^2-4=y | | 2(4z+2)-6=70 | | 3(t+2)=7(7-t)-9 | | 3x-4x+5=54 | | 3m+6=37 | | 12-2a=18 | | 4.75=1.75+1a | | 20X+32=0 | | 60=32-4(x-3) | | 3x+4z=13 |